Thermal performance of cold plates - Ang, Shao Wei (Nanyang Technological University, 2024)
This report explores the possibility of combining manifold microchannels together with jet impingement to improve on thermal capabilities of heat sink devices. Both manifold microchannels and jet impingement methods are widely used in the industry because of their practicality and effectiveness in cooling the heat sink. Hence, the author sims to combine both methods together to harness the benefits of both manifold microchannels and jet impingement methods.